Implementasi Penyisipan Pesan Teks Terenkripsi Menggunakan Kriptografi ElGamal pada Citra Digital Menggunakan Steganogarafi LSB - Elpridayanti Saragih; Dodi Siregar; Haida Dafitri (PRPM STMIK TRIGUNA DHARMA, 2023)
Message security is very important in maintaining the confidentiality of information, especially those containing important information whose contents should only be known by the entitled party. Therefore, security is needed for messages that are confidential so that messages cannot be intercepted by people who do not want them and the information content of the message becomes more secure. One way is to apply ElGamal and LSB cryptography methods to be able to provide security to text messages by inserting into digital images, the ElGamal algorithm focuses on the strength of the key in solving discrete logarithm problems. By utilizing large prime numbers and discrete logarithm problems which are quite difficult and also by applying the LSB method for text insertion, the security of the key is more guaranteed. The test results on five image objects with the .BMP extension on the application that was built were running well and correctly. The image that is inserted in the encryption process is the insertion of text in the image after it is decrypted and the image produced after the encryption and decryption process is no different from the original image and the same thing for the image size does not change